Digital sextortion: Internet predators and pediatric interventions. Issue 1 (February 2020) - Hong, Suyeon; Lu, Nancy; Wu, Doreen; Jimenez, David E.; Milanaik, Ruth L.
Abstract : Purpose of review: Sextortion is defined as the act of coercing people into sending explicit images of themselves and subsequently blackmailing victims with the public release of said images. Prosecutions of sextortion cases involving minors have increased almost two-fold in the past 5 years. The purpose of this review is to explore the literature regarding the behavior of both victims and perpetrators, the effects on victims, and the support resources available for clinicians, victims, and parents. Recent findings: Sextortion begins as an unassuming request for personal pictures and quickly escalates. Minors targeted by predators fear both punishment by guardians and the social consequences that follow the release of their explicit pictures. This cycle of victimization endangers minors and may lead to mental health problems, such as anxiety and depression. Recently, sextortion cases have risen to the forefront of national attention through the mainstream media with celebrities revealed as both perpetrators and victims. This higher visibility of sextortion highlights the importance of reviewing recent research regarding minors and their online behavior and the tactics of perpetrators. Summary: Sextortion, an extreme form of cyber abuse, endangers minors and may lead to anxiety and depression. Pediatricians should be familiar with the concept of sextortion and discuss its dangers and available resources with parents and minors. Abstract : Supplemental Digital Content is available in the text